Analysis of the Optimal Recombination Center Level to Adjust Rationally the 3 Main Parameters of p+nn+ Structure - Pak, Byong Su; Yu, Nam Chol; Chu, KyongIl; Ryang, KumJun (Journal of Power Electronics and Devices, 2022)
In this paper, we analyze of optimal recombination center level to adjust rationally the 3 main parameters of fast p+nn+ structure - forward voltage drop, reverse recovery time, and reverse current. The forward voltage drop of the p+nn+ structure is affected strongly by the high-level carrier lifetime. Reverse current is affected strongly by the low-level lifetime and reverses recovery time is affected strongly by the space-charge generation lifetime. These 3 carrier lifetimes influence 3 main parameters of p+nn+ structure differently. When we decrease the low-level carrier lifetime to decrease the reverse recovery time, the forward voltage drop increases, and when we increase the high-level carrier lifetime for reducing the forward voltage drop, the reverse recovery time increases. So, to adjust these conflicting relations, we will illuminate the recombination center level formed in the basic floor of the p+nn+ structure. On the other hand, to determine the recombination center level coincide with the practical recombination center level, we suggest the analytic method of determining the recombination center level formed by 2 carrier lifetime regulation sources.